Pannexin‐1 promotes NLRP3 activation during apoptosis but is dispensable for canonical or noncanonical inflammasome activation. Issue 2 (29th August 2019) - Chen, Kaiwen W.; Demarco, Benjamin; Broz, Petr
Abstract: Inflammasomes are multimeric protein complex that assemble in the cytosol upon microbial infection or cellular stress. Upon activation, inflammasomes drive the maturation of proinflammatory cytokines, IL‐1β and IL‐18, and also activate the pore‐forming protein, gasdermin D to initiate a form of lytic cell death known as "pyroptosis". Pannexin‐1 is channel‐forming glycoprotein that promotes membrane permeability and ATP release during apoptosis; and was implicated in canonical NLRP3 or noncanonical inflammasome activation. Here, by utilizing three different pannexin‐1 channel inhibitors and two lines of Panx1 –/– macrophages, we provide genetic and pharmacological evidence that pannexin‐1 is dispensable for canonical or noncanonical inflammasome activation. In contrast, we demonstrate that pannexin‐1 cleavage and resulting channel activity during apoptosis promotes NLRP3 inflammasome activation. Abstract : The contribution of pannexin‐1 to canonical and noncanonical inflammasome signaling is controversial. Here, we provide genetic and pharmacological evidence that pannexin‐1 is dispensable for canonical and noncanonical inflammasome activation; and canonical and noncanonical inflammasome activation does not trigger pannexin‐1 cleavage. In contrast, pannexin‐1 cleavage and resulting channel activity promotes NLRP3 inflammasome activation during apoptosis.